2016
DOI: 10.1016/j.cmi.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

European Society of Clinical Microbiology and Infectious Diseases: update of the diagnostic guidance document for Clostridium difficile infection

Abstract: In 2009 the first European Society of Clinical Microbiology and Infectious Diseases (ESCMID) guideline for diagnosing Clostridium difficile infection (CDI) was launched. Since then newer tests for diagnosing CDI have become available, especially nucleic acid amplification tests. The main objectives of this update of the guidance document are to summarize the currently available evidence concerning laboratory diagnosis of CDI and to formulate and revise recommendations to optimize CDI testing. This update is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
477
3
47

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(559 citation statements)
references
References 90 publications
15
477
3
47
Order By: Relevance
“…The contamination route can be explained by the manual handling of the tubes containing the isolated DNA and PCR mixture to the Rotor-Gene, which required placing caps on tiny tubes, arranged very close to each other. The sensitivity of both PCRs and specificity of the in-house PCR are in agreement with the NAAT performance in symptomatic C. difficile patients, as mentioned in the recently published European Society of Clinical Microbiology and Infectious Diseases (ESCMID) guidance document, with an overall sensitivity of 95% and specificity of 98% in comparison with TC (20). A discrepancy analysis was performed, mainly to clarify why conflicting test results were obtained.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The contamination route can be explained by the manual handling of the tubes containing the isolated DNA and PCR mixture to the Rotor-Gene, which required placing caps on tiny tubes, arranged very close to each other. The sensitivity of both PCRs and specificity of the in-house PCR are in agreement with the NAAT performance in symptomatic C. difficile patients, as mentioned in the recently published European Society of Clinical Microbiology and Infectious Diseases (ESCMID) guidance document, with an overall sensitivity of 95% and specificity of 98% in comparison with TC (20). A discrepancy analysis was performed, mainly to clarify why conflicting test results were obtained.…”
Section: Discussionmentioning
confidence: 70%
“…Guerrero et al showed that asymptomatic carriers have lower numbers of C. difficile in their rectal swab than CDI patients, indicating that stool samples should be preferred (4). Furthermore, a mix of diagnostic screening tests have been applied to detect C. difficile, frequently subdivided into assays to recognize toxigenic or nontoxigenic strains (20). However, a comparison of various diagnostic tests with a reference method to detect asymptomatic colonization of C. difficile has not been studied before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far there, are several reviews of the molecular methods developed to detect C. difficile toxins, and their use for diagnosis [100,107,110,111,[113][114][115]. In the last two years, some immunoassays have been developed [116][117][118][119] that can overcome the stagnation of C. difficile toxin detection.…”
Section: Difficile Toxinsmentioning
confidence: 99%
“…C. difficile polymerase chain reaction (PCR) is a highly sensitive test, though it does not distinguish colonization from active infection with a toxigenic strain, problematic if PCR is the sole means of diagnosis. Their center utilizes a two-step assay, which has been recommended in recently published clinical guidelines [14], with the enzyme immunoassay for toxins A and B enhancing specificity. Rates of C difficile colonization at the time of hospital admission are as high as 10% [15] possibly much higher in patients with IBD [16].…”
mentioning
confidence: 99%